Everyday referenced use of a digital temperature sensor – how well do alternative ice cubes really cool a drink? - Fleischer Timo; Feichtner Julia; Strauß Isabella; Strahl Alexander (Chemistry Teacher International, 2023)
In this paper, the cooling effect of alternative ice cubes made of granite, soapstone and ceramic is experimentally examined with the help of a digital temperature sensor and compared with that of a conventional ice cube. Digital sensors can be integrated in an everyday referenced way in the sense of inquiry-based learning during experimentation in chemistry lessons, since the use of ice cubes is a typical everyday situation that many students know and is therefore well suited for everyday referenced chemistry lessons. The advantages of digital sensors include the easy recording of measured values, the automatic creation of tables and graphs, and the direct link between the experiment and the representation. The results of the experiment reveal that the water ice cube has by far the greatest cooling effect compared to the alternative ice cubes. The entire cooling process of the ice cubes is explained and calculated, which essentially consists of three sub-steps: heating the ice cubes to melting temperature, melting the ice cubes, mixing the melted ice cube with the drink. The comparison of calculated and experimentally measured values shows that the cooling effect of all ice cubes could be determined very accurately experimentally using the digital temperature sensor.